Limbah kelapa sawit, Tandan kosong sawit, Pelepah sawit, Kompos, Pengelolaan limbah berkelanjutan - Nasriel Ikhsan; Aprilia Angraini; Athaya Haura Annasywa Hatuala; Wiranti Diah Wulandari; Hikmatul Hasana; Lora Hardiwiyana; Aulia Salsabila Putri; Yohanis Yarom Mate; Ahmad Ferdy Saputra; Danang Adi Putra (PT. Penerbit Riset Sadwa, 2026)
Waste management issues in Beriang Tinggi Village, Tanjung Kemuning District, Kaur Regency are caused by the absence of a well-mapped Temporary Disposal Site (TPS) and limited waste bin facilities, resulting in residents disposing of waste in inappropriate locations that pose a risk of environmental pollution. This community service activity aims to strengthen sustainable waste management systems through TPS point mapping and the construction of waste bins in the village. The method applied combines the Asset Based Community Development (ABCD) approach with Appropriate Technology (TTG) based on spatial mapping, implemented through four stages: preparation, spatial mapping of TPS points using GPS and GIS, construction of waste bins based on mapping results, and monitoring and evaluation. The results show that a distribution map of TPS points was produced as the basis for determining waste bin locations, and one waste bin unit was successfully built, equipped with organic waste sorting and a rocket stove, which has been utilized by residents for disposing of household waste. This approach, integrating spatial mapping with physical facility construction, proved effective in ensuring that waste bin placement was well-targeted and supportive of the sustainability of village-level waste management programs.